The TSA project in Germany: Results & Reactions - Gerd Ahlert (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2004)
In 2003 the Institute of Economic Structures Research (GWS mbH) has developed a tourism satellite account (TSA) for the Federal Republic of Germany relating to the year 2000.1 During the process of empirical compilation the Federal Statistical Office (as an external partner outside the GWS) has been fully integrated and provided partially unpublished data. In the first part of this paper some empirical results of the monetary TSA-tables T 1 to T 6 and the employment table T 7 for the German TSA are presented. In 2000, the gross value added of tourism activities of private households in Germany made up nearly 57.5 billion Euros, meaning a share of 3.2 % of the total gross value added. In the second part some first reactions and objections to the results are discussed. Mainly it focuses on the question whether the TSA concept respectively the present German TSA pilot version ascertain all relevant tourism activities.
Keywords: L83; 330; TSA; Germany; tourism satellite account; results; reactions